A rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel

By adopting rapid heat treatment methods on magnetically-deposition-free hardened stainless steel, including solid solution treatment, water cooling and aging treatment, the problems of strength improvement and time-consuming under traditional processes are solved, and the dual goals of high strength and efficient production are achieved.

CN119753292APending Publication Date: 2025-04-04BEIJING BEIYE FUNCTIONAL MATERIALS CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633593.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Under traditional heat treatment technology, it is difficult to improve the stainless steel without magnetic precipitation hardened under high strength requirements, and the process takes a long time and consumes a lot of manpower and material resources.

Method used

The rapid heat treatment method is adopted, including performing a solution treatment at the first set temperature, followed by water cooling, and aging treatment at the second set temperature to reduce the precipitation of the η phase and promote the precipitation and growth of the γ' strengthened phase.

Benefits of technology

The yield strength, tensile strength and hardness of non-magnetic precipitation hardened stainless steel are significantly improved, reaching performance levels of 1000MPa, 1250MPa, HV350 or above, while shortening the heat treatment time and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753292A_ABST
    Figure CN119753292A_ABST
Patent Text Reader

Abstract

The present application relates to a rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel, and belongs to the field of metal heat treatment. The method comprises: subjecting a stainless steel sample to a solid solution treatment at a first set temperature; subjecting the stainless steel sample to water cooling after the solid solution treatment; subjecting the stainless steel sample to an aging treatment after water cooling at a second set temperature, so as to reduce or avoid the precipitation of the η phase of the stainless steel sample, and promote the precipitation and / or growth of the γ' strengthening phase of the stainless steel sample, so as to obtain high-strength non-magnetic precipitation hardening stainless steel. Based on the traditional heat treatment process, the method effectively reduces the precipitation of unfavorable phases, promotes the precipitation and / or growth of the γ' strengthening phase, and greatly improves the yield strength, tensile strength and hardness of the non-magnetic precipitation hardening stainless steel by precisely controlling the solid solution temperature, solid solution time, aging temperature and aging time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal heat treatment, and in particular to a rapid heat treatment method for improving the strength of non-magnetic precipitation hardened stainless steel. Background Art

[0002] Non-magnetic stainless steel is usually austenitic stainless steel. Austenite has paramagnetism and weak response to magnetic field. This type of stainless steel achieves high strength by adding elements such as Mn and N and large deformation, and can also achieve high strength by adding elements such as Ti and Al and precipitation strengthening phase at low temperature. The matrix of non-magnetic precipitation hardening stainless steel is stable austenite. High strength is achieved by precipitation strengthening of γ' phase at 650-780℃. The γ' phase is a face-centered cubic ordered structure. Therefore, the alloy maintains high strength while still maintaining good non-magnetic properties. It is widely used in aerospace engine components, such as turbine disks, blades and other fasteners. my country began to develop this type of alloy in the 1960s, and the main types of products are bars, plates, strips, etc.

[0003] The composition of non-magnetic precipitation hardening stainless steel is similar to that of iron-based high-temperature alloys (such as domestic GH132 alloy and foreign A286 alloy), with slightly higher Cr and Ti contents, and no Mo. The strengthening mechanism and heat treatment process are consistent with GH132 and A286. The traditional heat treatment process is high-temperature solid solution + aging, that is, 980℃ for 1h solid solution and 720℃ for 16h aging. Under the traditional heat treatment process, in addition to the austenite matrix, γ' strengthening phase, TiC and TiN inclusions, the alloy may also have η phase at the grain boundary. The η phase will hinder the formation of the γ' strengthening phase to a certain extent. It has a lamellar structure under the microscope. It is easy to grow into the grain during the heat treatment process. The lamellar structure is easy to cause intergranular cracks, which is not conducive to the improvement of the strength of non-magnetic precipitation hardening stainless steel. The generation of η phase should be avoided as much as possible during heat treatment to promote the formation of γ' phase.

[0004] In the existing industrial production, after obtaining the finished products of non-magnetic precipitation hardened stainless steel bars, plates and strips, they must first be kept at 980℃ for 1 hour to eliminate the effects of hot working or cold working, so that the alloy elements are fully dissolved and the alloy structure is homogenized, and then they are kept at 720℃ for 16 hours for aging to make the γ' strengthening phase precipitate and grow, thereby achieving high strength to achieve its application under different conditions. However, a large number of organizational analyses have shown that this type of stainless steel is on the verge of η phase precipitation under traditional heat treatment processes, which hinders the improvement of stainless steel strength, and the aging process of keeping at 720℃ for 16 hours is too time-consuming and consumes a lot of manpower and material resources. Non-magnetic precipitation hardened stainless steel is widely used in various fields such as aerospace, shipbuilding, and automobiles due to its excellent mechanical properties and non-magnetic characteristics. The yield strength, tensile strength, and hardness after traditional heat treatment can be maintained at around 750MPa, 1050MPa, and HV300, and the magnetic permeability μ 100Below 1.006Gs / Oe. With the rapid development of my country's aerospace industry and the research and development of large civil aircraft, the market has put forward higher requirements for non-magnetic stainless steel, requiring yield strength, tensile strength, and hardness to be above 1000MPa, 1250MPa, and HV350. Although nickel-based high-temperature alloys can achieve this strength requirement, the cost is relatively high. Summary of the invention

[0005] The present application provides a rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel to solve the following technical problem: how to improve the strength of non-magnetic precipitation hardening stainless steel.

[0006] The present application provides a rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel, the method comprising:

[0007] The stainless steel sample is solution treated at a first set temperature;

[0008] The stainless steel sample after solution treatment is water-cooled;

[0009] The water-cooled stainless steel sample is subjected to aging treatment at a second set temperature to reduce or avoid the precipitation of the η phase of the stainless steel sample and promote the precipitation and / or growth of the γ' strengthening phase of the stainless steel sample to obtain high-strength non-magnetic precipitation-hardened stainless steel.

[0010] Optionally, the high-strength non-magnetic precipitation-hardened stainless steel meets at least one of the following properties: yield strength ≥1000 MPa, tensile strength ≥1250 MPa and Vickers hardness ≥350.

[0011] Optionally, the first set temperature is 845°C to 855°C.

[0012] Optionally, the heating rate of the solution treatment is 15°C / min to 50°C / min.

[0013] Optionally, the holding time of the solution treatment is 25 min to 35 min.

[0014] Optionally, the water cooling temperature is 10°C to 40°C.

[0015] Optionally, the second set temperature is 775°C to 785°C.

[0016] Optionally, the heating rate of the aging treatment is 15°C / min to 50°C / min.

[0017] Optionally, the insulation time of the aging treatment is 2h to 4h.

[0018] Optionally, the chemical composition of the high-strength non-magnetic precipitation hardened stainless steel includes, by mass fraction: C≤0.08%, Si≤0.80%, Mn≤0.80%, Ni: 25.00%~27.00%, Cr: 13.50%~18.00%, Ti: 1.90%~3.50%, Al: 0.20%~0.35%, V: 0.10%~0.50%, Fe.

[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0020] The present application provides a rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel, the method comprising: subjecting the stainless steel sample to solution treatment at a first set temperature; subjecting the stainless steel sample to water cooling after the solution treatment; subjecting the stainless steel sample to aging treatment after water cooling at a second set temperature to reduce or avoid the precipitation of the η phase of the stainless steel sample, and promote the precipitation and / or growth of the γ' strengthening phase of the stainless steel sample, thereby obtaining high-strength non-magnetic precipitation hardening stainless steel. Based on the traditional heat treatment process, the method effectively reduces the precipitation of unfavorable phases and promotes the precipitation and / or growth of the γ' strengthening phase by precisely controlling the solution temperature, solution time, aging temperature and aging time. The γ' phase is an important precipitation strengthening phase that can significantly improve the yield strength, tensile strength and hardness of the material. Therefore, the yield strength, tensile strength and hardness of the treated non-magnetic precipitation hardening stainless steel are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0023] Figure 1 A schematic flow chart of a rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel provided in an embodiment of the present application;

[0024] Figure 2 A comparison diagram of the microstructures of high-strength non-magnetic precipitation-hardened stainless steel obtained by the rapid heat treatment method provided in the embodiment of the present application and the traditional heat treatment method. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0026] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0027] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the weight ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the weight of substance A: the weight of substance B: the weight of substance C = 1:2:3.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0029] Figure 1 A schematic flow chart of a rapid heat treatment method for improving the strength of non-magnetic precipitation hardened stainless steel provided in an embodiment of the present application.

[0030] See also Figure 1 The present application provides a rapid heat treatment method for improving the strength of non-magnetic precipitation hardening stainless steel, the method comprising:

[0031] S1, subjecting the stainless steel sample to solution treatment at a first set temperature;

[0032] Solution treatment and aging treatment are two commonly used heat treatment processes in metal material processing, each of which has a specific purpose and operating process.

[0033] Solution treatment refers to a heat treatment process in which the alloy is heated to a high temperature single-phase region and kept at a constant temperature, so that the excess phase is fully dissolved into the solid solution and then rapidly cooled to obtain a supersaturated solid solution. During the solution process, the solid solution elements in the alloy will be uniformly dissolved in the matrix to form a solid solution with a solid solution strengthening effect. This uniform solid solution structure can improve the plasticity and toughness of the alloy, while eliminating the intergranular brittleness in the alloy and improving the creep resistance. Solution treatment can also eliminate the inhomogeneity of the structure and performance of metal materials after cold deformation, so that they have better processability and comprehensive performance.

[0034] Solution treatment can eliminate the stress generated by the alloy during hot and cold processing, and make the alloy recrystallize, thereby improving its plasticity and toughness. A supersaturated solid solution will be formed in the alloy after solution treatment, and this solid solution will precipitate fine strengthening phases under appropriate conditions, thereby improving the strength and hardness of the alloy.

[0035] The equipment for solution treatment can be a box-type heat treatment furnace. The heat treatment furnace is heated at a certain heating rate. After reaching the temperature, the stainless steel sample is placed. The stainless steel sample can be a finished product of stainless steel bars, plates and strips. After the solution treatment, the sample is immediately taken out of the heat treatment furnace, sent into water for water cooling, and taken out after being cooled to room temperature.

[0036] In some embodiments, the first set temperature is 845°C to 855°C.

[0037] The temperature range of 845°C to 855°C can ensure that the alloying elements (such as chromium, nickel, titanium, vanadium, etc.) in the stainless steel are fully dissolved in the austenite matrix to form a uniform solid solution. This not only creates favorable conditions for subsequent aging treatment, but also effectively reduces the structural heterogeneity in the material. Exemplarily, the first set temperature can be 845°C, 847°C, 849°C, 851°C, 853°C, 855°C, etc.

[0038] In some embodiments, the heating rate of the solution treatment is 15° C. / min to 50° C. / min.

[0039] Controlling the heating rate of 15°C / min to 50°C / min helps improve production efficiency. For example, the heating rate of the solution treatment can be 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, 45°C / min, 50°C / min, etc.

[0040] In some embodiments, the holding time of the solution treatment is 25 min to 35 min.

[0041] The holding time of 25min to 35min is set to ensure that the alloy elements have enough time to diffuse and dissolve during the solution treatment process, so as to achieve the purpose of structural homogenization. This helps to eliminate component segregation and microstructural defects inside the material and improve the overall performance of the material. Exemplarily, the holding time of the solution treatment can be 25min, 27min, 29min, 31min, 33min, 35min, etc.

[0042] The combination of strict control of the solution treatment temperature and the holding time of the solution treatment can significantly improve the strength and hardness of non-magnetic precipitation hardened stainless steel. The solution treated material can form a finer and more evenly distributed precipitate phase during the subsequent aging treatment process. These precipitates will act as strengthening particles to hinder dislocation movement, thereby significantly improving the mechanical properties of the material. By strictly limiting the solution treatment temperature and holding time, the controllability and repeatability of the heat treatment process can be ensured, making the performance of the final non-magnetic precipitation hardened stainless steel more stable and reliable.

[0043] S2, water cooling the stainless steel sample after the solution treatment;

[0044] In some embodiments, the water cooling temperature is 10°C to 40°C.

[0045] Water cooling temperature control of 10℃~40℃ helps to quickly cool the material to room temperature after solution treatment, reducing the coarsening of the structure caused by too slow cooling rate. A faster cooling rate helps to obtain a finer structure, thereby improving the strength and toughness of the material. Exemplarily, the water cooling temperature can be 10℃, 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, etc.

[0046] S3. Performing aging treatment on the water-cooled stainless steel sample at a second set temperature to reduce or avoid the precipitation of the η phase of the stainless steel sample and promote the precipitation and / or growth of the γ' strengthening phase of the stainless steel sample to obtain high-strength non-magnetic precipitation hardened stainless steel.

[0047] Aging treatment refers to the process of keeping the metal or alloy workpiece at a relatively low temperature for a period of time after solution treatment (or cold plastic deformation, casting, forging, etc.) to allow the alloy elements that were originally dissolved in the matrix in the solid solution state to re-precipitate and form dispersed precipitates. The formation of these precipitates can greatly improve the hardness, strength and wear resistance of the alloy material, and also improve its corrosion resistance. The time and temperature of aging treatment have an extremely important impact on the performance of the alloy. A reasonable aging process can enable the alloy to achieve the best performance.

[0048] Aging treatment can eliminate the internal stress generated by metals or alloys during processing and prevent deformation or cracking caused by internal stress. Through aging treatment, the organization and size of metals or alloys can be stabilized, improving their reliability during use. Aging treatment can also further improve the strength, hardness and other mechanical properties of metals or alloys.

[0049] As the main strengthening phase, the presence of a large amount of γ' phase can significantly improve the yield strength and tensile strength of the material. The precipitation and / or growth of γ' phase also helps to improve the hardness of the material and meet the high hardness requirements.

[0050] After water cooling to room temperature, aging treatment is carried out. The aging treatment equipment can be a box-type heat treatment furnace. The heat treatment furnace is heated at a certain heating rate. After reaching the temperature, the sample is placed. After aging treatment, the sample is taken out of the heat treatment furnace and cooled to below 40°C in the air.

[0051] In some embodiments, the second set temperature is 775°C to 785°C.

[0052] At an aging treatment temperature of 775°C to 785°C, the strengthening phase in the alloy can be fully precipitated and dispersed in the matrix. These fine strengthening phases can significantly improve the yield strength, tensile strength and hardness of the material, meeting or exceeding the predetermined mechanical property requirements. Exemplarily, the second set temperature can be 775°C, 777°C, 779°C, 781°C, 783°C, 785°C, etc.

[0053] In some embodiments, the heating rate of the aging treatment is 15° C. / min to 50° C. / min.

[0054] A heating rate of 15°C / min to 50°C / min can shorten the time it takes for the heating furnace to heat to the target temperature, thereby improving the efficiency of the entire heat treatment process, which is of great significance for large-scale production and increasing production capacity.

[0055] In some embodiments, the holding time of the aging treatment is 2 hours to 4 hours.

[0056] The holding time is 2h to 4h. Appropriate holding time can ensure the full precipitation of the strengthening phase and avoid the performance degradation caused by over-aging. For example, the holding time of the aging treatment can be 2h, 2.5h, 3h, 3.5h, 4h, etc.

[0057] In some embodiments, the high-strength non-magnetic precipitation hardened stainless steel meets at least one of the following properties: yield strength ≥1000 MPa, tensile strength ≥1250 MPa and Vickers hardness ≥350.

[0058] The present application reduces or avoids the precipitation of η phase and promotes the precipitation and / or growth of γ' strengthening phase by lowering the solution temperature in the traditional heat treatment, shortening the solution time, increasing the aging temperature, shortening the aging time, making the obtained high-strength non-magnetic precipitation hardened stainless steel have a yield strength of ≥1000MPa, a tensile strength of ≥1250MPa and a Vickers hardness of ≥350. For example, the yield strength can be 1000MPa, 1020MPa, 1040MPa, 1060MPa, 1080MPa, 1100MPa, 1120MPa, etc.; the tensile strength can be 1250MPa, 1270MPa, 1290MPa, 1310MPa, 1330MPa, 1350MPa, 1370MPa, etc.; the Vickers hardness can be 350, 355, 360, 365, 370, 375, 380, etc.

[0059] In some embodiments, the chemical composition of the high-strength non-magnetic precipitation hardening stainless steel includes, by mass fraction: C≤0.08%, Si≤0.80%, Mn≤0.80%, Ni: 25.00%~27.00%, Cr: 13.50%~18.00%, Ti: 1.90%~3.50%, Al: 0.20%~0.35%, V: 0.10%~0.50%, Fe.

[0060] The positive effect of limiting C≤0.08% is: C≤0.08% helps to reduce the formation of carbides in stainless steel, thereby reducing the sensitivity to intergranular corrosion and improving the overall corrosion resistance of the material. C≤0.08% can reduce brittle phases in the material, such as carbides, thereby improving the toughness and impact resistance of stainless steel. In addition, during the solution treatment process, C≤0.08% helps to obtain a more uniform austenite structure, providing a better foundation for subsequent aging treatment, which is conducive to the precipitation and distribution of the γ' strengthening phase, thereby improving the strength and hardness of the material. C≤0.08% helps to reduce the formation of ferrite, thereby maintaining the non-magnetic or low magnetic properties of stainless steel to meet the needs of specific applications. Exemplarily, the C content can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, etc.

[0061] Positive effects of limiting Si ≤ 0.80%: Maintaining high strength and hardness, silicon can improve the strength and hardness of stainless steel, but a silicon content higher than 0.80% may increase the brittleness of the material and reduce its toughness and processing properties. Therefore, limiting the silicon content to ≤ 0.80% helps maintain good toughness while maintaining high strength and hardness of the material. Exemplarily, the Si content can be 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, 0.80%, etc.

[0062] Positive effects of limiting Mn ≤ 0.80%: The Mn element has a certain solid solution strengthening effect in stainless steel, but a Mn content higher than 0.80% may cause excessive ferrite or other non-austenite phases in the material, thereby affecting the material's non-magneticity and strength. Limiting the Mn content to ≤ 0.80% helps maintain the austenite stability of the material, promotes the formation of uniform and fine austenite structure, and provides favorable conditions for the precipitation of the γ' strengthening phase during the subsequent aging treatment. Exemplarily, the Mn content can be 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, 0.80%, etc.

[0063] The positive effect of limiting the Ni content to 25.00% to 27.00% is that Ni is an austenite-forming element, and a Ni content of 25.00% to 27.00% helps stabilize the austenite structure and improve the yield strength and tensile strength of the material. Ni can also improve the corrosion resistance of stainless steel, allowing it to maintain stable performance in harsh environments. For example, the Ni content can be 25.00%, 25.50%, 26.00%, 26.50%, 27.00%, etc.

[0064] Positive effects of limiting the Cr content to 13.50% to 18.00%: Chromium is one of the most important alloying elements in stainless steel and has a decisive influence on the corrosion resistance of stainless steel. Chromium can form a dense chromium oxide (Cr2O3) film on the surface of the material, effectively preventing the intrusion of corrosive media such as oxygen and water, thereby improving the corrosion resistance of stainless steel. This feature is particularly important in non-magnetic precipitation hardening stainless steel because it ensures the stability of the material in a variety of harsh environments. In addition, the addition of chromium helps to stabilize the microstructure of stainless steel, especially at high temperatures. During high-temperature solution treatment and aging treatment, chromium helps to maintain the stability of microstructures such as austenite or martensite, prevent adverse phase changes, and thus ensure the mechanical properties of the final product. Exemplarily, the Cr content can be 13.50%, 14.50%, 15.50%, 16.50%, 17.50%, 18.00%, etc.

[0065] Positive effects of limiting the Ti content to 1.90% to 3.50%: For example, controlling the Ti content within the range of 1.90% to 3.50% helps to form a stable precipitation phase and further improve the strength and hardness of the material. The Ti content can be 1.90%, 2.10%, 2.30%, 2.50%, 2.70%, 3.10%, 3.30%, 3.50%, etc.

[0066] The positive effect of limiting the Al content to 0.20% to 0.35% is that aluminum is one of the important elements in stainless steel to improve corrosion resistance. Aluminum can work synergistically with the chromium element in steel to form a denser oxide film, which can effectively prevent oxygen, water and other corrosive media from corroding the steel, thereby improving the corrosion resistance of stainless steel. In addition, the compounds or precipitates formed by aluminum and other elements in stainless steel can significantly increase the hardness of the material. These hard precipitates play a role of dispersion strengthening inside the material, so that non-magnetic precipitation hardened stainless steel has a higher hardness while maintaining high strength. Exemplarily, the Al content can be 0.20%, 0.23%, 0.25%, 0.27%, 0.29%, 0.31%, 0.33%, 0.35%, etc.

[0067] The positive effect of limiting the V content to 0.10% to 0.50% is that vanadium is a strong carbide-forming element and can form fine carbide (such as VC) precipitation phases in stainless steel. These precipitation phases play a role of dispersion strengthening in the material and can significantly improve the strength and hardness of the material. By controlling the vanadium content within the range of 0.10% to 0.50%, the number, distribution and morphology of these precipitation phases can be optimized to obtain the best strengthening effect. Exemplarily, the V content can be 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, etc.

[0068] The specific content / content range of Fe can be obtained by the upper and lower limit formula of the component, namely:

[0069] The sum of the percentages of the contents of each component in a composition should be equal to 100%, and the content ranges of several components should meet the following conditions: the upper limit value of a component + the lower limit value of other components ≤ 100; the lower limit value of a component + the upper limit value of other components ≥ 100.

[0070] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0071] Example 1

[0072] (1) Solution heating: A box-type heat treatment furnace is used for solution treatment, with a heating rate of 20°C / min and the temperature is raised to 850°C.

[0073] (2) Solution insulation: After the heat treatment furnace reaches temperature, put the sample in and start insulation at 850℃.

[0074] (3) Solution cooling: After keeping the sample for 30 min, take it out of the heat treatment furnace immediately and put it into water for water cooling at 25 °C. Then take it out after rapid cooling.

[0075] (4) Aging heating: A box-type heat treatment furnace is used for aging treatment, with a heating rate of 20°C / min and the temperature is raised to 780°C.

[0076] (5) Aging and insulation: After the heat treatment furnace reaches temperature, put the sample in and start insulation at 780℃.

[0077] (6) Aging cooling: After keeping warm for 2.5 h, take the sample out of the heat treatment furnace and cool it to below 40 °C in air.

[0078] (7) Organization analysis and performance testing: After obtaining the aged samples, metallographic samples, tensile samples, and hardness samples were made by machining, and then organization analysis and mechanical property testing were performed. No η phase was precipitated in the organization, and all precipitated phases were uniformly dispersed γ' strengthening phases. The mechanical property test results are shown in Table 1.

[0079] Example 2

[0080] (1) Solution heating: A box-type heat treatment furnace is used for solution heat treatment at a heating rate of 25°C / min to a temperature of 845°C.

[0081] (2) Solution insulation: After the heat treatment furnace reaches temperature, put the sample in and start insulation at 845℃.

[0082] (3) Solution cooling: After keeping the sample for 35 min, take it out of the heat treatment furnace immediately and put it into water for water cooling at 30 °C. Then take it out after rapid cooling.

[0083] (4) Aging heating: A box-type heat treatment furnace is used for aging treatment, with a heating rate of 25°C / min and the temperature is raised to 783°C.

[0084] (5) Aging and insulation: After the heat treatment furnace reaches temperature, put the sample in and start insulation at 783℃.

[0085] (6) Aging cooling: After keeping warm for 3 h, take the sample out of the heat treatment furnace and cool it to below 40 °C in air.

[0086] (7) Organization analysis and performance testing: After obtaining the aged samples, metallographic samples, tensile samples, and hardness samples were made by machining, and then organization analysis and mechanical property testing were performed. No η phase was precipitated in the organization, and all precipitated phases were uniformly dispersed γ' strengthening phases. The mechanical property test results are shown in Table 1.

[0087] Example 3

[0088] (1) Solution heating: A box-type heat treatment furnace is used for solution treatment at a heating rate of 30°C / min to a temperature of 855°C.

[0089] (2) Solution insulation: After the heat treatment furnace reaches temperature, put the sample in and start insulation at 855℃.

[0090] (3) Solution cooling: After keeping the sample for 30 min, take it out of the heat treatment furnace immediately and put it into water for water cooling at 20 °C. Then take it out after rapid cooling.

[0091] (4) Aging heating: A box-type heat treatment furnace is used for aging treatment, with a heating rate of 30°C / min and the temperature is raised to 778°C.

[0092] (5) Aging and insulation: After the heat treatment furnace reaches temperature, put the sample in and start insulation at 778℃.

[0093] (6) Aging cooling: After keeping warm for 4 h, take the sample out of the heat treatment furnace and cool it to below 40 °C in air.

[0094] (7) Organization analysis and performance testing: After obtaining the aged samples, metallographic samples, tensile samples, and hardness samples were made by machining, and then organization analysis and mechanical property testing were performed. No η phase was precipitated in the organization, and all precipitated phases were uniformly dispersed γ' strengthening phases. The mechanical property test results are shown in Table 1.

[0095] Table 1 Mechanical properties test results

[0096] Group Yield strength(MPa) Tensile strength(MPa) Vickers hardness Example 1 1069 1316 379 Example 2 1101 1325 375 Example 3 1099 1326 379

[0097] It can be seen from Table 1 that the process parameters involved in the rapid thermal treatment method of the embodiment are all within the required range of the present invention, with yield strength ≥1000 MPa, tensile strength ≥1250 MPa and Vickers hardness ≥350.

[0098] Attached Figure 2 Detailed description:

[0099] Figure 2 The microstructure comparison diagram of the high-strength non-magnetic precipitation hardened stainless steel obtained by the rapid heat treatment method provided in the embodiment of the present application and the traditional heat treatment method is as follows: Figure 2 As shown, in the high-strength non-magnetic precipitation hardened stainless steel obtained by the rapid heat treatment method provided in the embodiment of the present application, all the precipitated phases are relatively large-sized γ' strengthening phases, which significantly improves the yield strength, tensile strength and hardness of the stainless steel.

[0100] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0101] (1) The rapid heat treatment process of the present invention is simple and efficient, shortening the heat treatment time to about 8 hours, saving 12 hours compared with the traditional heat treatment process, increasing the efficiency by 60%, and greatly reducing the heat treatment cost.

[0102] (2) After the non-magnetic precipitation hardened stainless steel is treated by the heat treatment process of the present invention, the mechanical properties are improved, and the yield strength, tensile strength and hardness are increased to 1000MPa, 1250MPa, HV350 or above, which can fully support the rapid development of aerospace, automobile and other fields, save raw material costs, and create greater economic benefits.

[0103] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A rapid heat treatment method for improving the strength of non-magnetic precipitation hardened stainless steel, the method comprising: The stainless steel sample is solution treated at a first set temperature; The stainless steel sample after solution treatment is water-cooled; The water-cooled stainless steel sample is subjected to aging treatment at a second set temperature to reduce or avoid the precipitation of the η phase of the stainless steel sample and promote the precipitation and / or growth of the γ' strengthening phase of the stainless steel sample to obtain high-strength non-magnetic precipitation-hardened stainless steel.

2. The method according to claim 1, characterized in that The high-strength non-magnetic precipitation hardened stainless steel meets at least one of the following properties: yield strength ≥1000MPa, tensile strength ≥1250MPa and Vickers hardness ≥350.

3. The method according to claim 1, characterized in that The first set temperature is 845°C to 855°C.

4. The method according to claim 1, characterized in that: The heating rate of the solution treatment is 15°C / min to 50°C / min.

5. The method according to claim 1 or 4, characterized in that: The holding time of the solution treatment is 25 min to 35 min.

6. The method according to claim 1, characterized in that The water cooling temperature is 10°C to 40°C.

7. The method according to claim 1, characterized in that The second set temperature is 775°C to 785°C.

8. The method according to claim 1, characterized in that The heating rate of the aging treatment is 15°C / min to 50°C / min.

9. The method according to claim 1 or 8, characterized in that: The heat preservation time of the aging treatment is 2h to 4h.

10. The method according to claim 1, characterized in that Measured by mass fraction, the chemical composition of the high-strength non-magnetic precipitation hardening stainless steel includes: C≤0.08%, Si≤0.80%, Mn≤0.80%, Ni: 25.00%~27.00%, Cr: 13.50%~18.00%, Ti: 1.90%~3.50%, Al: 0.20%~0.35%, V: 0.10%~0.50%, Fe.